Florida Master Beekeeper Program Requirements - James D. Ellis; Jerry Hayes; Catherine M. Zettel Nalen; William H. Kern; Ray Zerba; Brad Burbaugh (EDIS, 2010)
ENY155, a 9-page fact sheet by James Ellis, Jerry Hayes, Catherine Zettel Nalen, William H. Kern, Ray Zerba, and Brad Burbaugh, describes the requirements for this beekeeper training and certification program provided by the University of Florida. Published by the UF Department of Entomology and Nematology, May 2010.